The politics of migration and mobility in the art world: transnational Baltic artistic practices across Europe. - Duester, Emma (Intellect Books Ltd, 2021)
Explores the nature of artistic practices for highly mobile artists from the Baltic States, moving regularly across multiple borders across Europe in order to maintain their position on the global art world. Artists with trans-local homes that combine and connect homeland, host country and a unique understanding of home and belonging. 12 b/w illus.